The Effectiveness of Live Streaming Shopping Attributes on Shopee Live in Jakarta - Anastasya, Yohana (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
Business actors must understand what attributes they need to focus on to increase live streaming shopping views and sales to run successfully. This study aims to determine the level of effectiveness of Live Streaming Shopping Attributes on Shopee Live in DKI Jakarta with a case study on fashion products. This research is a type of quantitative research with a survey method through filling out a Google Form questionnaire. The sample in this study used a non-probability sampling method with purposive sampling technique. The data analysis techniques used in this study are simple tabulation analysis, descriptive analysis, and average score. Based on the results of data analysis, the Live Streaming Shopping Attributes are categorized as "Very Good" and "Very Effective", supportted by Price and Promotion Attributes and Seller Presentation, Seller Interactivity, and Seller Guidance Attributes. After conducting research on the effectiveness of Live Streaming Shopping Attributes (LSSA) on Shopee Live in Jakarta, it is concluded that the effectiveness of LSSA is effective in making viewers live streaming shopping on Shopee Live watch to make purchase transactions on fashion products.